PENGARUH PENDEKATAN OPEN-ENDED TERHADAP SELF-ESTEEM DAN HASIL BELAJAR MATEMATIKA SISWA KELAS VII DI SMP NEGERI 10 LANGSA - Malayati. I, Sofiyan, Fadilah (Universitas Samudra, 2020)
This study aims at determining whether there is an influence of open-ended approach to mathematics learning outcomes of and finding out how the influence of the open-ended approach to self-esteem of seventh grade students in SMP Negeri 10 Langsa. This study uses a quantitative experimental research with one-group pretest-posttest design. An experiment with one-group pretest-posttest is a type of research that does not apply a controlgroup or only uses one group, yet it administrates a pre and post-test for that group. From the hypothesis test results, it was obtained that t (count)> t (table) where at a significant level of 95% t value = 10,032> then H0 is rejected and Ha is accepted. Besides, at a significant level of 99% t value = 10,032> then H0 is rejected and Ha is accepted. The two significant levelsshow that H0: rejected and Ha: accepted. It means that there is an influence of open-ended approach toward mathematics learning outcomes of seventh grade students inSMP Negeri 10 Langsa. Based on the calculation result of questioner, the average percentage of students was 43%. In other words, this shows that the average percentage of students learning mathematics over self-esteem is 43%. It means that nearly half of students already have self-esteem or confidence in learning mathematics by using open-ended approach.